2023
DOI: 10.1177/03000605231184046
|View full text |Cite
|
Sign up to set email alerts
|

Association with controlling nutritional status score and disease activity of ulcerative colitis

Ziyu Lian,
Jingyi Hu,
Cheng Cheng
et al.

Abstract: Objective To explore the association between the controlling nutritional status (CONUT) score and disease activity in patients with ulcerative colitis (UC). Methods This retrospective study enrolled patients with UC. Demographic, clinical and laboratory data were collected and compared. The CONUT score was obtained for each patient. The association between the CONUT score and laboratory parameters was analysed and the ability of the score to assess disease activity was evaluated. Results A total of 182 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Several studies analyzed potential methods of predicting outcomes in the treatment of UC; while most assessed outcomes in acute severe colitis [ASC] and for the need for colectomy at initial presentation and subsequent ASC-related hospital admissions [ 21 , 22 ], others focused on factors such as biomarkers [ 23 ], nutritional status [ 24 , 25 ], age [ 26 , 27 ], rate of steroid or biological treatment response [ 28 , 29 ] in light of clinical outcomes and disease severity during treatment. Previous research identified anemia and the need for early corticosteroid therapy as predictors for complicated UC [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies analyzed potential methods of predicting outcomes in the treatment of UC; while most assessed outcomes in acute severe colitis [ASC] and for the need for colectomy at initial presentation and subsequent ASC-related hospital admissions [ 21 , 22 ], others focused on factors such as biomarkers [ 23 ], nutritional status [ 24 , 25 ], age [ 26 , 27 ], rate of steroid or biological treatment response [ 28 , 29 ] in light of clinical outcomes and disease severity during treatment. Previous research identified anemia and the need for early corticosteroid therapy as predictors for complicated UC [ 30 ].…”
Section: Discussionmentioning
confidence: 99%